Physical activity and quality of life of elderly people participating in extension programs university during the covid-19 pandemic (Citizenship in Action: Extension and Culture Magazine, 2024)
Aim: To investigate the association between self-perceived level of physical activity and health-related quality of life (HRQoL) in Brazilian elderly during the COVID-19 pandemic. Methodology: This is a cross-sectional study involving 274 elderly individuals from public university extension programs in southern Brazil. The level of physical activity (PA) was assessed through self-perception using the question "How do you rate your level of physical activity during the pandemic?" HRQoL was assessed using the 12-item Health Survey. Data were analyzed using one-way analysis of variance and multiple logistic regression (p < 0.05). Results: The mean age of the elderly participants was 71.2 ± 6.33 years, with 244 women and 30 men. The results indicated that active elderly individuals, according to their self-perceived PA level, had higher scores in all HRQoL components and domains compared to elderly individuals who self-identified as insufficiently active or inactive (p < 0.001). In logistic regression, the adjusted model identified that insufficiently active elderly individuals were more likely to have reduced HRQoL in all components (p < 0.001). Regarding domains, these elderly individuals had 4.44 (95% CI: 2.47-7.99) and 4.84 (95% CI: 2.51-8.02) times greater odds of having reduced physical and mental domains, respectively. Conclusion: elderly people who considered themselves physically active during the COVID-19 pandemic have a better quality of life compared to those who perceive themselves as insufficiently active or inactive. Furthermore, elderly people who consider themselves insufficiently active or physically inactive were more likely to have a reduced quality of life during the period of social isolation. Demonstrating the impact of the level of physical activity on the quality of life of this population during the Covid-19 pandemic. This denotes the importance of these extension programs for the quality of life of this population and the social bias of Universities given their potential to promote community health..
Keywords: physical activity; covid 19 pandemic; elderly; community extension